Innovation for transition to a circular economy : a transdisciplinary case study at Distell - Woolls-King, Monique (Stellenbosch : Stellenbosch University, 2017)
ENGLISH SUMMARY : The negative effects of excessive global resource use see the urge for decoupled methods of consumption. The circular economy has been acknowledged as a tool to mitigate continued resourced exploitation, and could provide a method for countries to transition towards sustainability. This thesis investigates whether the application of the circular economy may facilitate broader systemic change that provides economic, environmental and social benefits in the context of South Africa. More locally, this thesis responds to the impending closure of the Stellenbosch landfill site, and aims to explore a practical solution to help divert waste from landfill. This thesis aims to fulfil two main objectives. First, it aims to synthesise both transitions theory and the circular economy to provide an innovative tool with which to approach sustainable transitions. Second, it aims to apply this hybrid theory in a transdisciplinary case study at Distell to uncover an innovative closed-loop waste solution. Other objectives aim to contribute to Distell’s ongoing sustainability efforts, respond to Stellenbosch Municipality’s target of reducing organic waste to landfill, contribute to the growing research and evidence of the circular economy and its outcomes, motivate continued theory development and empirical research into the potential synthesis of the two theories and initiate the academic discourse of the circular economy in South Africa. The two main objectives are explored by analysing two sub-questions in two freestanding journal articles. The first article explores the potential synthesis of the fields of the circular economy and transitions theory through a literature review. Although these theories are clearly different, the argument is made that the strengths in the one theory can bolster the weaknesses in the other. The intersection between the two distinct theories has the potential to facilitate a sustainable transition towards a circular economy through innovation. The general conditions under which the circular economy may be replicable is suggested, and further research is recommended to investigate this lens in a case study. The amalgamated theory provides the conceptual tool used to analyse the transdisciplinary case study at Distell in article two. The case study investigates the various waste stream opportunities at Distell that can demonstrate the synthesis in article one to provide a scalable intervention with environmental, social and economic benefits. The filter waste stream was chosen due its high priority given by Distell, and with the conceptual tool it was possible to design a closed loop intervention that has the potential for widespread positive environmental, economic and social effects. Closing the loop on the cellulose filter waste entails using them to grow and sell edible mushrooms, thereafter selling or using the exhausted substrate as compost. The implications could include two new revenue streams, reduced costs, waste diverted from landfill, reduced greenhouse gas emissions associated with landfilling, soil regeneration, increased carbon sequestration ability of soils, strategic positional advantages and semi and low-skilled job creation. Since the majority of the Western Cape wineries use the same filter method, these findings could potentially transform the Western Cape wine industry, and thus our soils. The specific conditions under which this intervention could be replicable is suggested, and further research is recommended to develop a clear strategy for implementing this project, and to continue the theory development of the amalgamation of transitions theory and the circular economy.